What variables are connected with system usability and satisfaction? Results from an educational virtual reality field trip - Maximilian C. Fink; Volker Eisenlauer; Bernhard Ertl (Computers & Education: X Reality, 2023)
Exploring the usability of educational virtual reality (VR) is essential. Research in this area can explain the adoption of VR as a new technology, contribute to examining paths toward effective learning, and provide recommendations for effective educational design. This study investigated usability in a sample of N = 64 university students learning about simplified construction engineering topics from an interactive VR field trip. Two research objectives were pursued. First, the level of achieved usability was examined using a mixed-methods approach, including data from semi-structured interviews and a survey on system usability and satisfaction. Second, the relationships between several connected variables (ease of use, usefulness, presence, and cognitive load) and system usability and satisfaction were investigated quantitatively. With respect to the first research objective, system usability and satisfaction were evaluated positively in the interviews and rated highly in the surveys. These results indicate that VR field trips, which are increasingly replacing excursions, are regarded as an appropriate instructional method. Concerning the second research objective, ease of use, usefulness, presence, and extraneous load were found to predict system usability. Further, the factors of usefulness, presence, and intrinsic cognitive load helped explain the variance in satisfaction. These findings highlight that the variables connected to system usability and satisfaction in VR learning vary. In addition to these and other theoretical implications, practical implications and recommendations for educational design are discussed.